Pengaruh Media Sosial Tiktok Terhadap Perilaku Konsumtif Remaja Di Kawasan Kolong Tol Penjaringan, Jakarta Utara - Jefry Robert Dianto; Vidya Kusumawardani (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2026)
This study aims to analyze the influence of the social media platform TikTok on the consumer behavior of teenagers in the Penjaringan toll underpass area, North Jakarta. The research uses a quantitative approach with an explanatory survey method on 30 active TikTok-using teenagers. Data were collected through questionnaires and analyzed using simple linear regression with the help of IBM SPSS Statistics 25. The results show that TikTok has a significant impact on teenage consumer behavior with a significance value of 0.008 (<0.05). The regression equation obtained is Y = 21.048 + 0.364X, indicating a positive relationship between TikTok usage and consumer behavior. The coefficient of determination (R Square) value of 0.225 shows that TikTok contributes 22.5% to teenage consumer behavior, while 77.5% is influenced by other factors outside the study. These findings indicate that the higher the intensity of TikTok use, the higher also the tendency for teens to have consumptive behavior. Keywords: TikTok, social media, consumptive behavior, adolescents, Penjaringan.